Meningkatkan Hasil Belajar Bahasa Indonesia Materi Mendeskripsikan Benda Secara Tertulis dengan Menggunakan Media Gambar - Dominika Dua Siska; Marianus Yufrinalis; Lukas Bera (Departement of Mathematics Education, 2023)
This study aims to improve the ability to describe objects using media images in class II students at SDK Waiara. This research is a classroom action research (CAR) designed to help teachers (researchers) find and solve learning problems that occur in class. This class action research will be carried out in cycles, between cycles I and II. Presentation of completeness cycle I was 47.058% and cycle II increased to 94.177%. student achievement, especially in the subject of Indonesian describing objects. This shows that learning to improve the ability to describe objects using media images in Indonesian subjects can be further applied to improve student achievement, especially in Indonesian subjects describing objects